Biological impact of cigarette smoke compared to an aerosol produced from a prototypic modified risk tobacco product on normal human bronchial epithelial cells. Issue 8 (December 2015) - Kogel, U.; Gonzalez Suarez, I.; Xiang, Y.; Dossin, E.; Guy, P.A.; Mathis, C.; Marescotti, D.; Goedertier, D.; Martin, F.; Peitsch, M.C.; Hoeng, J.
Highlights Systems toxicology analyses were used to compare an MRTP with a reference cigarette. Lower volatile constituent concentrations in MRTP than in cigarette smoke extract. Less cell stress and death occurred with MRTP than 3R4F at equal concentrations. Less Nrf2 signaling occurred with MRTP than 3R4F at equal concentrations. Less network perturbation occurred with MRTP than 3R4F at equal concentrations.